Eye dreaming : photographs by Anthony Barboza - Barboza, Anthony, 1944-; Bryant, Aaron; Harris, Mazie M. (J. Paul Getty Museum, 2022)
"An introduction to the work and life of celebrated photographer and artist Anthony Barboza"--